Pengaruh Religiusitas, IGCG, dan Motivasi Terhadap Kepercayaan Muzaki Pada Amil Zakat Surabaya - Pratiwi, Dini Wahyu; Ajib Ridlwan, Ahmad (Universitas Negeri Surabaya, 2019)
This study aims to determine effect of religiosity in islamic perspective, Islamic good corporate governance, and motivation in islamic perspective towards Muzakki’s trust to zakat institution in Surabaya. This study used quantitative method with data collecting from questionnaire distributing to 100 respondents. Object of this study is Muzakki, who already made zakat payment to zakat institution in Surabaya that has been registered in National Zakat Forum. Analysis method that was used is multiple regression analysis. The finding shows that effect of Islamic religiosity, Islamic good corporate governance and Islamic motivation has particially sicnificant towards Muzakki’s trust to zakat institution in Surabaya.